ANALISIS VISI MISI INSTITUT AGAMA ISLAM SAHID DALAM MEWUJUDKAN ISLAMIC ENTREPRENEURIAL UNIVERSITY - Dewi Purwati (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2023)
Islamic religious tertiary institutions are expected to produce graduates who are qualified and have an entrepreneurial spirit who are able to create jobs. Likewise, an Islamic educational institution, in this case the Private Islamic Religious College (PTKIS), especially the Bogor Sahid Islamic Institute (INAIS), must continue to strive to improve quality in an effort to maintain its existence and survive amidst the very tight competition in the world of education today. . To achieve these ideal conditions, higher education institutions in general and in this case INAIS must clearly have a vision and mission that are in line with today's, tomorrow's and future needs. The purpose of this study is to analyze the Vision and Mission of the Sahid Islamic Institute in Creating an Islamic Entrepreneurial University. The type of research used is qualitative research with a descriptive analytical case study approach and library research. The results in the study show that the Vision and Mission of the Sahid Islamic Institute in Creating an Islamic Entrepreneurial University has not been fully achieved because there are obstacles faced by the Sahid Islamic Institute, one of which is because there are many graduate or alumni professions who are not entrepreneurs so that a strategy is needed, namely to improve education. and teaching, research and community service as well as supported by infrastructure that supports the achievement of entrepreneurial competence.